Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Cerita Matematika SD Kelas V Berdasar Newman Error Analysis - Ekadayanti, Waode; Saputra, Erwin Eka; Fista, Bela; Yanti, Noer Rakhmat (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2024)
The purpose of this research is to find out the types and factors that cause student errors in solving math word problems for class V SD based on Newman error analysis. This type of research is descriptive qualitative research using a qualitative approach. Data collection techniques in this study used tests, interviews and documentation where the instrument used was a 4-item essay test, while the interviews were conducted by the class teacher to find out the factors that caused students' mistakes in solving math word problems. VB class students at SDN 4 Ranomeeto, totaling 25 people, were the subjects of this study. The results of this study indicate that students' ability to solve math word problems is still very low. Based on the NEA, the most student errors lie in comprehension errors (comprehension errors) 74 errors out of 25 students with 4 items followed by transformation errors with 7 errors then process skill errors with 2 errors and finally errors writing the final answer (encoding error) with 7 errors. It can be concluded that in solving math word problems based on the Newman error analysis error, most students made mistakes in understanding the problem.